The effect of tetracyclines on quantitative measures of osteoclast morphology. - Zaidi, M; Moonga, B; Huang, C; Towhidul Alam, A; Shankar, V; Pazianas, M; Eastwood, J; Datta, H; Rifkin, B (Kluwer Academic Publishers-Plenum Publishers, 1993)
We report the effects of the tetracycline analogues 4-dedimethylaminotetracycline (CMT-1) and minocycline on osteoclast spreading and motility. Both agents influenced the morphometric descriptor of cell spread area, rho, producing cellular retraction or an R effect (half-times: 30 and 44 minutes for CMT-1 and minocycline, respectively). At the concentrations employed, the tetracycline-induced R effects were significantly slower than, but were qualitatively similar to, those resulting from Ca2+ "receptor" activation through the application of 15 mM-[Ca2+] (slopes: -1.25, -0.18, and -4.40/minute for 10 mg/l-[CMT-1], 10 mg/l-[minocycline] and 15 mM-[Ca2+], respectively). In contrast, the same tetracycline concentrations did not influence osteoclast margin ruffling activity as described by mu, a motility descriptor known to be influenced by elevations of cellular cyclic AMP. Thus, the tetracyclines exert morphometric effects comparable to changes selectively activated by occupancy of the osteoclast Ca2+ "receptor" which may act through an increase in cytosolic [Ca2+].